2005
DOI: 10.4049/jimmunol.175.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing IL-7 Availability on Lymphocytes during and after Lymphopenia-Induced Proliferation

Abstract: IL-7 is critically involved in regulating peripheral T cell homeostasis. To investigate the role of IL-7 on lymphopenia-induced proliferation of polyclonal lymphocytes, we have transferred CFSE-labeled cells into a novel T-lymphopenic, IL-7-transgenic mouse line. Results obtained indicate that T and B cells do not respond in the same way to IL-7-homeostatic signals. Overexpression of IL-7 enhances proliferation of both CD4+ and CD8+ T cells but with distinctly temporal effects. Expansion of naturally arising C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
1
34
0
1
Order By: Relevance
“…Altogether, our results suggest that IL-7R expression on regulatory CD4 + T cells may be too low to enable them to respond to the IL-7 levels reached in a lymphopenic environment. In line with this hypothesis, it was shown that regulatory CD4 + T cells are able to proliferate in vivo in response to the high levels of IL-7 reached in IL-7-transgenic mice or in mice injected with high concentrations of exogenous IL-7/anti-IL-7 complexes (41,42).…”
Section: Regulatory Cd4 + T Cells Receive Help From Conventional Cd4 mentioning
confidence: 58%
“…Altogether, our results suggest that IL-7R expression on regulatory CD4 + T cells may be too low to enable them to respond to the IL-7 levels reached in a lymphopenic environment. In line with this hypothesis, it was shown that regulatory CD4 + T cells are able to proliferate in vivo in response to the high levels of IL-7 reached in IL-7-transgenic mice or in mice injected with high concentrations of exogenous IL-7/anti-IL-7 complexes (41,42).…”
Section: Regulatory Cd4 + T Cells Receive Help From Conventional Cd4 mentioning
confidence: 58%
“…Clearly, during an ongoing antiviral immune response, some degree of priming is seen among mature thymocytes (25,26). Using either parabiosis (6) or transfer of CFSE-labeled cells (27), we have previously shown that in a situation of peripheral lymphopenia, the contribution of recirculating peripheral T cells to the pool of mature "thymocytes" was significant. Using complementary approaches, including adoptive transfer of genetically marked T cells and the intrasplenic injection of CFSE, in this study we quantify this recirculation in detail and analyze the phenotype and TCR V␤ repertoire of recirculating cells.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10][11] In animal models of lymphopenia, administration of IL-7 can facilitate restoration of lymphocyte homeostasis even in the presence of high serum levels of IL-7 and low T-cell IL-7 receptor levels. 12 Despite its central role in B-cell lymphopoiesis in the mouse, the role of IL-7 in human B-cell lymphopoiesis is not considered essential. 3,13 The fundamental roles of IL-7 in thymopoiesis, maturation, survival, and differentiation of T cells provided the rationale for testing this cytokine as an immune adjuvant therapy in HIV infection.…”
Section: Introductionmentioning
confidence: 99%